Anaplastic pancreatic cancer: presentation, surgical management, and outcome - Strobel, Oliver; Hartwig, Werner; Bergmann, Frank; Hinz, Ulf; Hackert, Thilo; Grenacher, Lars; Schneider, Lutz; Fritz, Stefan; Gaida, Matthias; Büchler, Markus W.; Werner, Jens (Surgery, 2011)
Background - Anaplastic pancreatic cancers are rare neoplasms. The available data are focused on pathologic and molecular features, and little is known about the clinical presentation and management. The outcome of operative exploration and resection is unknown. - Methods - From a prospective database, all consecutive operations for anaplastic pancreatic cancer performed at our institution were identified. The clinicopathologic details were analyzed and the outcome was compared with a matched group of typical pancreatic ductal adenocarcinomas (nested case-control study). - Results - Eighteen patients with anaplastic pancreatic cancer were identified. The patients had a median age of 64 years. The tumors were large (median diameter, 4 cm) and showed peripheral contrast enhancement in radiologic imaging. Fifteen (83%) patients underwent resection, a palliative bypass procedure was performed in 1 (6%) patient, and 2 patients underwent exploration with biopsy only. Perioperative morbidity was 39% and mortality was 6%. The median survival rate in patients with anaplastic pancreatic cancer was 5.7 months and was less than in the control group of patients with pancreatic ductal adenocarcinoma (15.7 months). In anaplastic pancreatic cancer, the median duration of survival was significantly greater after R0/R1 resection, as compared with palliative surgery (7.1 vs 2.3 months). The duration of survival was significantly greater in neoplasms with osteoclast-like giant cells. In 3 (17%) patients, long-term survival of 33, 49, and 161 months was observed. - Conclusion - Anaplastic pancreatic cancer is an aggressive type of pancreatic cancer with a short median survival; however, because of the observation of prolonged survival after resection, resection should be performed whenever possible. The presence of osteoclast-like giant cells is associated with a favorable prognosis.
Online verfügbar 9 Juni 2010
Gesehen am 24.10.2022